2022
DOI: 10.5603/dk.a2022.0031
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peer Group-Based Training Using Health Belief Model on Quality of Life and Foot Ulcer Self-Care Behaviour in Patients with Type 2 Diabetes: A Randomized Controlled Clinical Trial

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In this study, peers were identified as playing a role in developing adolescent perceptions of perceived obstacles and benefits, thereby supporting the formation of adolescent motivation in acting or behaving. Peers can encourage positive behavior by increasing positive behavior in taking care actions (Tazangi et al, 2022). This phenomenon is inseparable from the character of adolescents who prioritize peer groups in making decisions.…”
Section: Peersmentioning
confidence: 99%
“…In this study, peers were identified as playing a role in developing adolescent perceptions of perceived obstacles and benefits, thereby supporting the formation of adolescent motivation in acting or behaving. Peers can encourage positive behavior by increasing positive behavior in taking care actions (Tazangi et al, 2022). This phenomenon is inseparable from the character of adolescents who prioritize peer groups in making decisions.…”
Section: Peersmentioning
confidence: 99%